Intergenerational Transmission of Human Capital: Is It a One-Way Street? - Petter Lundborg; Kaveh Majlesi (Lund University, School of Economics and Management, Department of Economics, 2015)
Studies on the intergenerational transmission of human capital usually assume a one-way spillover from parents to children. But what if children also affect their parents' human capital? Using exogenous variation in education, arising from a Swedish compulsory schooling reform in the 1950s and 1960s, we address this question by studying the causal effect of children's schooling on their parents' longevity. We first replicate previous findings of a positive and significant cross-sectional relationship between children's education and their parents' longevity. Our causal estimates tell a different story; children's schooling has no significant effect on parents' survival. These results hold when we examine separate causes of death and when we restrict the sample to low-income and low-educated parents.
Keywords: I10; I21; I26; J14; 330; Intergenerational transmission; Human capital; Longevity; Compulsory schooling; Education